(untitled) (Journal of Management and Business Education, 2019)
In this contribution, we give empirical evidence on our experience on the usage of webinars as a tool to complement teaching in the classroom in the framework of high university level education in economics and business. We design an ad-hoc survey to know the percentage of students who, before the experience, are familiar to the tool before the experience as well as the preferences of the students after the experience between “traditional presentations” and “webinars” We have also students’ feedback on the acquisition of competences. Being the experience implemented in different groups and using two alternative apps, we contrast whether the results are contingent of the group-subject and/or the tool. Results show an increase in the percentage of students that would choose using webinar instead of traditional presentations after the experience. Students admit showing lower levels of stage fright, being better trained to use other new technologies in the future and, feeling better trained for their future professional career. Moreover, recognise that webinar could give some dynamism to the teaching process in the classroom. Results are not contingent of the subject either the digital tool used to arrange the webinar.